2015
DOI: 10.1016/j.smallrumres.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Milkability and milking efficiency improvement in Murciano-Granadina breed goats

Abstract: The aim of this study was to verify the effect of cluster, udder characteristics and milking 21 parameters on milkability and milking efficiency of Murciano-Granadina breed goats, in 22 order to improve them. The cluster used is well adapted to the goats, except that the teat-floor 23 distance is too short for the teat-cup used and the cluster rests on the platform instead of 24 hanging from the udder, something apparently attributed to a poor udder conformation rather 25 than an excessively long teat-cup. Udd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…From the mean value of MF1 in our experiment (0.67 kg/min) and the mean latency time values obtained (T0: 4.9 s; T1: 15.8 s), we can estimate an approximate MF1r of 0.8 kg/min. This latter value is similar to the MF1r of 0.8 to 0.9 kg/min obtained with electronic meters by Fernández et al (2015) in Murciano-Granadina goats from an experimental station, with 1 daily milking and a 2 L/d milk yield. In other research into this breed in experimental stations, notably lower MF1r values were obtained (0.44 kg/min, Peris et al, 1996; 0.61 kg/min, Manzur et al, 2012), possibly because the animals used presented a lower average milk production (0.5 L in the afternoon milking with 2 milkings daily and 1 L in single milking, respectively).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From the mean value of MF1 in our experiment (0.67 kg/min) and the mean latency time values obtained (T0: 4.9 s; T1: 15.8 s), we can estimate an approximate MF1r of 0.8 kg/min. This latter value is similar to the MF1r of 0.8 to 0.9 kg/min obtained with electronic meters by Fernández et al (2015) in Murciano-Granadina goats from an experimental station, with 1 daily milking and a 2 L/d milk yield. In other research into this breed in experimental stations, notably lower MF1r values were obtained (0.44 kg/min, Peris et al, 1996; 0.61 kg/min, Manzur et al, 2012), possibly because the animals used presented a lower average milk production (0.5 L in the afternoon milking with 2 milkings daily and 1 L in single milking, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…The time spent on milking depends on the number of milking sessions daily (1 or 2 in goats) and the hourly performance of milkers (goats milked per man and hour). In turn, this latter aspect is influenced by several factors related to the animals' ability for milking, the milking machine and parlor, the milking routine, and skill of the operators (Manzur et al, 2012;Bueso-Ródenas et al, 2014;Fernández et al, 2015). The animal's milkability conditions the time spent extracting its milk from the udder, which in turn is related on one hand with those udder features affecting the speed at which the different milking operations are carried out (teatcup attachment, machine stripping, and frequency of slipping or falling teatcups) and, on the other, the milk production and flow during machine milking.…”
Section: Introductionmentioning
confidence: 99%
“…There is recent evidence (Blasco et al, 2016) that mechanical milking of Murciano-Granadina goats is performed excessively slowly, with mean milk flows between 600 and 700 mL/min. This is much lower than the 939 mL/min reported by Le Du and Benmederbel (1984) despite the need for a 35-kPa average vacuum to open the teat sphincter in Saanen goats versus the 30.1-kPa average vacuum (Fernández et al, 2015) for Murciano-Granadina breed goats. In an initial exploratory work (Fernández et al, 2015), we found that the problem of slow milking does not seem to reside in the milking machine materials but rather in the high sphincter strength of the animals and that the solution lay in increasing the vacuum level (kPa) or pulsator rate (cycles per minute; cpm) or both.…”
Section: Introductionmentioning
confidence: 53%
“…This is much lower than the 939 mL/min reported by Le Du and Benmederbel (1984) despite the need for a 35-kPa average vacuum to open the teat sphincter in Saanen goats versus the 30.1-kPa average vacuum (Fernández et al, 2015) for Murciano-Granadina breed goats. In an initial exploratory work (Fernández et al, 2015), we found that the problem of slow milking does not seem to reside in the milking machine materials but rather in the high sphincter strength of the animals and that the solution lay in increasing the vacuum level (kPa) or pulsator rate (cycles per minute; cpm) or both. The values of the different parameters commonly used for the mechanical milking of Murciano-Granadina goats range between 40 and 42 kPa, 90 and 120 cpm, and 60 and 66% in terms of kilopascals of vacuum level, cmp of pulsator rate, and percentage of pulsator ratio, respectively (Díaz et al, 2012;Hamzaoui et al, 2013;Blasco et al, 2016).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation